Effect of Combined Local-Point Electroacupuncture and Auricular Acupuncture Therapy on Pain Scale and Straight Leg Raise (SLR) Changes in Farmers with Radiating Low Back Pain at the Healthy Family Independent Acupuncture Practice, Kepahiang, Bengkulu - sufi, varradiba; Eka Putri, Kurnia; Widyastari, Sri; Aulia Abdullah, Dona (HAKTI : Indonesian Acupuncture Therapists Association, 2025)
Low back pain radiating to the legs, or radiculopathy, is a condition that involves multiple nerve roots, resulting in pain as well as motor and sensory disturbances. Electroacupuncture and auricular acupuncture are known to reduce pro-inflammatory cytokines and stimulate the release of serotonin, norepinephrine, and endorphins, thereby accelerating the healing process of radiating low back pain. This study aimed to determine the effect of combined local-point electroacupuncture and auricular acupuncture therapy on changes in pain scale (NRS) and straight leg raise (SLR) among farmers with radiating low back pain at the Healthy Family Independent Acupuncture Practice, Kepahiang, Bengkulu. A quasi-experimental design with a two-group pre-test–post-test approach was employed, using a purposive sampling technique. The results showed that the combination of electroacupuncture and auricular acupuncture significantly affected changes in pain scale and straight leg raise (SLR) (p <0.001). The average reduction in NRS was 3.3, while the average increase in SLR was 33%. In conclusion, combined local-point electroacupuncture and auricular acupuncture therapy significantly improved pain scale and straight leg raise (SLR) outcomes among farmers with radiating low back pain